When you are mine : [compact disc, unabridged] a novel - Robotham, Michael, 1960- (Simon & Schuster Audio, 2022)
Philomena McCarthy has defied the odds and become a promising young officer with the Metropolitan Police despite being the daughter of a notorious London gangster.